Histopathological examination of tissues following a surgical uterine evacuation in the first trimester bleeding: clinical relevance - Khanal, Bandana; Sharma, Basant; Tamrakar, Renuka; Singh, Prekshya (Journal of Chitwan Medical College, 2020)
Background: There is no general consensus about the role of routine HPE of the obtained tissue at the time of uterine evacuation. However, it is understood clinically that it is of utmost importance to prove the presence of intrauterine gestation and to exclude gestational trophoblastic disease in the form of partial or complete mole. This study aimed to assess the role of histopathology in cases of first trimester miscarriages and to determine clinical relevance of histopathological examination following surgical evacuation. Methods: This was a retrospective study of collected data over 12 months (January 2018- December 2018) in an agency for reproductive health setup with predefined inclusion criteria. We included 60 consecutive patients attended with history of first trimester bleeding. Patient’s record and the histopathological examination report of products of conception following uterine evacuation were observed. The data was analyzed descriptive statistics including percentage, stander deviation, mean, and range in Microsoft Excel software. Results: Missed abortion was the most common type and constituted 55% of the studied group. The histopathological reports confirmed the pregnancy in all patients and revealed partial mole in 6(10%) patients and complete mole in 2(3.33%) patients. Conclusions: Histopathological examination of products of conception detects under diagnosed molar pregnancies that necessitates special follow up and is a key step to do further management.